Determining Formula Feeding Risk Factors: The Effect of Income and Education on Exclusive Breastfeeding Adherence in Rural Communities - Dyah Anggun Prameswari; Sri Lestariningsih (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Attempts to raise the prevalence of exclusive breastfeeding in rural areas continue to face obstacles when it comes to formula feeding infants ages 0–6 months. The use of formula milk is still widespread despite national policies that support exclusive breastfeeding; this is due to sociodemographic factors like family income and educational attainment. Through respiratory infections, impaired cognitive development, intestinal issues, and the possibility of stunting, these factors may endanger the health of children. In places like Puskesmas Donomulyo, which is surrounded by rural areas, some families still have limited access to health services and information, so economic and educational factors are the primary determinants of whether to breastfeed or use formula. This study aimed to identify the variables associated with formula feeding in infants aged 0–6 months in the Donomulyo Community Health Center area. A quantitative, retrospective case-control design is used in this investigation. The unpaired categorical analytic formula with Zα 0.96 and Zβ 0.84 was used to determine the sample. Using a straightforward random sampling method, 68 respondents in total were chosen based on inclusion and exclusion criteria. In order to determine the 95% confidence level and a significant level of p ˂ 0.05, the analysis employed the chi-square test and the computation of proportions in each category. Of the mothers who gave formula milk to their infants between the ages of 0 and 6 months, 58.8% had a supportive attitude, 67.6% had a supportive attitude, 64.7% worked, 52.9% had a high parental income, and 58.8% had support from health professionals. Results of statistical tests for maternal education (p value = 0.001; OR 5.510), attitude (p value = 0.002; OR 5.018), employment (p value = 0.004; OR 4.400), parental income (p value = 0.013; OR 3.656), and health worker support (p value = 0.225; OR 1.810). There was no correlation between formula feeding and health worker support in infants aged 0–6 months; however, a correlation was found between the mother's occupation, attitude, education, and parents' income. It is recommended that healthcare professionals provide ongoing education regarding the dangers of formula feeding and the significance of exclusive breastfeeding. Health professionals' home visits, regular counseling at Posyandu, and the activation of mothers' study groups can all contribute to achieving this goal. Particularly in rural areas with limited access to information, this strategy seeks to improve breastfeeding motivation, increase maternal understanding, and lessen reliance on formula milk